Kinesin‐14 is Important for Chromosome Segregation During Mitosis and Meiosis in the Ciliate Tetrahymena thermophila - Kushida, Yasuharu; Takaine, Masak; Nakano, Kentaro; Sugai, Toshiro; Vasudevan, Krishna Kumar; Guha, Mayukh; Jiang, Yu‐Yang; Gaertig, Jacek; Numata, Osamu (The Journal of eukaryotic microbiology, 2017)
Ciliates such as Tetrahymena thermophila have two distinct nuclei within one cell: the micronucleus that undergoes mitosis and meiosis and the macronucleus that undergoes amitosis, a type of nuclear division that does not involve a bipolar spindle, but still relies on intranuclear microtubules. Ciliates provide an opportunity for the discovery of factors that specifically contribute to chromosome segregation based on a bipolar spindle, by identification of factors that affect the micronuclear but not the macronuclear division. Kinesin‐14 is a conserved minus‐end directed microtubule motor that cross‐links microtubules and contributes to the bipolar spindle sizing and organization. Here, we use homologous DNA recombination to knock out genes that encode kinesin‐14 orthologues (KIN141, KIN142) in Tetrahymena. A loss of KIN141 led to severe defects in the chromosome segregation during both mitosis and meiosis but did not affect amitosis. A loss of KIN141 altered the shape of the meiotic spindle in a way consistent with the KIN141's contribution to the organization of the spindle poles. EGFP‐tagged KIN141 preferentially accumulated at the spindle poles during the meiotic prophase and metaphase I. Thus, in ciliates, kinesin‐14 is important for nuclear divisions that involve a bipolar spindle.